Smart Textile and Polymer Materials - Zhou, Yang; Li, Zhaoling (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book, entitled "Smart Textile and Polymer Materials", is dedicated to recent research and development regarding smart textiles and response-based polymer materials, including, but not limited to, fiber-based energy harvesting devices, energy storage devices, chromatic devices, color and shape changes, sensing, drug release, and ultraviolet resistant, electrically conductive, optical, hydrophobic and flame-retardant materials.